Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2015
DOI: 10.1115/gt2015-42144
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Analytical and Numerical Approach to Analyze Mud Motor Excited Vibrations in Drilling Systems

Abstract: Severe vibrations in drillstrings and bottomhole assemblies can be caused by cutting forces at the bit or mass imbalances in downhole tools. One of the largest imbalances is related to the working principle of the so-called mud motor, which is an assembly of a rotor that is maintained by the stator. One of the design-related problems is how to minimize vibrations excited by the mud motor. Simulation tools using specialized finite element methods (FEM) are established to model the mechanical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fatigue is brought on due to a combination of cyclical loading and temperature weakening (Ba et al 2016). Delpassand (1999), Gamboa et al (2003), Hohl et al (2015), and Ba et al 2016 At 100% efficiency, such as that found in lab-scale drilling, it was found that the MSE would equal the rock compressive strength (Teale 1965). In the special case of ductile rather than brittle material failure, MSE will be roughly three times rock strength (Rafatian et al 2009).…”
Section: Fig 3: Illustration Of Stator and Rotor Configuration (Dyckmentioning
confidence: 99%
“…Fatigue is brought on due to a combination of cyclical loading and temperature weakening (Ba et al 2016). Delpassand (1999), Gamboa et al (2003), Hohl et al (2015), and Ba et al 2016 At 100% efficiency, such as that found in lab-scale drilling, it was found that the MSE would equal the rock compressive strength (Teale 1965). In the special case of ductile rather than brittle material failure, MSE will be roughly three times rock strength (Rafatian et al 2009).…”
Section: Fig 3: Illustration Of Stator and Rotor Configuration (Dyckmentioning
confidence: 99%